(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
The experiment was carried out during the 2019/2020 season in a citrus orchard south of Tartous city on Citrus sinensis L.var.Valencia trees aged 12 years(which budded on Sour orange rootstock), to study the impact of foliar spray with salicylic acid (150 mg/l),citric acid(500 mg/l), potassium sulfate (2500 mg/l) and Fe(Fe-EDDHA) chelates (500 mg/l) on the physical and chemical properties of Valencia oranges. Foliar spray treatments were applied three times according to the phenological stages of trees. The results showed that the treatments significantly raised fruit volum and the percent of juice compared to the control, Salicylic acid spray gave the highest percent of juice (48%), Citric acid spray achieved the highest fruit size (212.57 cm3). Salicylic acid and citric acid treatments gave best results of ascorbic acid content (49.3, 48.25 mg/100 ml) respectively. The results showed that salicylic acid and citric acid sprays were more effective than potassium sulfate and iron chelate sprays in term of the studied parameters